2020
DOI: 10.1371/journal.pone.0231892
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of complement pathway activation with Pozelimab, a fully human antibody to complement component C5

Abstract: Complement is a key component of the innate immune system. Inappropriate complement activation underlies the pathophysiology of a variety of diseases. Complement component 5 (C5) is a validated therapeutic target for complement-mediated diseases, but the development of new therapeutics has been limited by a paucity of preclinical models to evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) properties of candidate therapies. The present report describes a novel humanized C5 mouse and its utility in eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
3
23
0
2
Order By: Relevance
“…Pozelimab is a fully human anti-complement C5, designed for the potential treatment of PNH and CD-55 deficient protein-losing enteropathy (CHAPLE disease) (NCT04209634). The molecule showed to be more potent in decreasing C5 levels and hemolysis in humans and animal models compared to eculizumab and ravulizumab [110], pushing its further investigation for the treatment of PNH and other complement-mediated diseases. Finally, a PEGylated anti-C5 aptamer, avacincaptad pegol sodium (Zimura ® ), is also under active development in a phase 2/3 trial in patients with geographic atrophy secondary to dry age-related macular degeneration (AMD) [111].…”
Section: Targeting C5mentioning
confidence: 99%
“…Pozelimab is a fully human anti-complement C5, designed for the potential treatment of PNH and CD-55 deficient protein-losing enteropathy (CHAPLE disease) (NCT04209634). The molecule showed to be more potent in decreasing C5 levels and hemolysis in humans and animal models compared to eculizumab and ravulizumab [110], pushing its further investigation for the treatment of PNH and other complement-mediated diseases. Finally, a PEGylated anti-C5 aptamer, avacincaptad pegol sodium (Zimura ® ), is also under active development in a phase 2/3 trial in patients with geographic atrophy secondary to dry age-related macular degeneration (AMD) [111].…”
Section: Targeting C5mentioning
confidence: 99%
“…This fully humanized antibody against C5 has been shown to suppress C5 levels and hemolysis in human serum and mice models in a more potent manner compared to eculizumab and ravulizumab ( 154 , 155 ). In a Phase 1 study in healthy subjects, pozelimab also showed 70% bioavailability after subcutaneous administration, allowing for more versatile administration options, such as weekly subcutaneous 400 mg administrations after a 15 mg/kg intravenous loading dose ( 156 ).…”
Section: Terminal Complement Pathway-targeting Treatments Of Inflammamentioning
confidence: 99%
“…[44]. D'autres anticorps ciblant la molécule C5, tels que le pozélimab (Regeneron Pharmaceuticals, Inc.) [45], le tésidolumab (Novartis) [46], le crovalimab/SKY59 (Chugai Pharmaceutical/Roche) [47], et l'ABP 959 (Alexion Pharmaceuticals) [48], sont aussi testés dans des essais cliniques pour le traitement de la COVID19.…”
Section: Figure 2 Rôle Des Inhibiteurs De La Cascade Du Complément Auunclassified